ANALISIS KUALITATIF FAKTOR PERILAKU SEKSUAL PRANIKAH REMAJA BERDASARKAN TEORI PERILAKU LAWRENCE GREEN (Studi Kasus di Wilayah Kerja Puskesmas Cilembang Kota Tasikmalaya) - Firdaus, Anisah Rahmah; Saraswati, Dian; Gustaman, Rian Arie (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
Adolescence is a period of transition from children to adults. Adolescence is a period of transition from children to adults. Behavior that leads to intimacy, sexual attraction and sexual habits carried out by two people of the same sex or the opposite sex before a legal marriage is called premarital sex behavior. This study aims to determine what factors can influence adolescent premarital sexual behavior based on the behavioral theory of Lawrence Green and Sarwono and how it impacts. The method in this research is a qualitative method with a case study approach. Informants are teenage girls who have premarital sex. The results of this study indicate predisposing factors for premarital sexual behavior, namely lack of knowledge, increased sexual libido, emotions, expectations, enabling factors for sexual behavior, namely the use of technological developments and information that is not wise. Reinforcing factors for sexual behavior are the attitudes of parents who taboo on sex, attitudes of peers that have a negative influence, delaying the age of marriage, tabooing sex, sexual violence, role vacancies, economics, conditions for joining the group. The impact of this sexual behavior is depression, low self- esteem, reproductive organ disorders, STD, pregnancy out of wedlock, sex addiction, regret, decreased school performance, social sanctions, sex becomes a teenage lifestyle, and sexual deviations. Therefore, to overcome this, it takes a wise attitude from parents, the community, health workers, and the youth themselves, so that they can get through the transition period safely.